Rock, Cowley County - Lindner-Goldenstein, Katie (Kansas State University, The Chapman Center for Rural Studies, 2019)
Rock is a small town situated southeast of Wichita between Augusta and Winfield. Established in 1869, Rock's population increased rapidly before peaking in 1887. In its heyday, the town boasted multiple shops, restaurants, and other businesses. This study uses the stories of various citizens to illustrate life in Rock throughout its long and varied history.
Katie Lindner-Goldenstein, “Rock, Cowley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/208.
Keywords: Cowley County; Douglass; Kansas; Rock; Santa Fe Railroad; Winfield